Behavioural economies in development decision making - Nel, Paul (Department of Construction Economics and Management, 2025)
This paper will research why businesses fail, the human connection to business failure – especially in the real estate market – and how to plan for success in real estate developments. It is important to understand the heuristics or rule of thumb of what, why and how an individual is driven to make certain decisions, their personality traits, past experiences and biases, how historic data can assist in predicting future market events, the variables thereof, and the use of traditional finance models within these paradigms.